Detection of atrial fibrillation in patients with cryptogenic stroke: The Nordic Atrial Fibrillation and Stroke (NOR-FIB) study - topline results. (19th May 2022) - Ratajczak-Tretel, B; Tancin Lambert, A; Hoie, GA; Al-Ani, R; Russell, D; Atar, D; Aamodt, AH
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): NOR-FIB is an investigator driven academic study. 100 of 259 devices are supported by Medtronic. BRT and ATL are recipients of a PhD grants from the South-Eastern Norway Regional Health Authority. The study is supported by the research infrastructure of the European Cerebrovascular Research Infrastructure (ECRI). Background: Cardioembolism due to occult atrial fibrillation (AF) is one of the common causes often identified by additional investigations in patients with cryptogenic stroke (CS). A large proportion of recurrent cerebral infarctions caused by AF can probably be prevented if more patients receive optimal cardiac monitoring after CS and TIA. Purpose: The aim of the prospective observational multi-center NOR-FIB study was to detect and quantify AF in patients with cryptogenic stroke or TIA under continuous 12 months cardiac rhythm monitoring with an implantable cardiac monitor (ICM) and to possibly identify biomarkers predicting incident AF. Methods: Patients with cryptogenic stroke and TIA diagnosed after state-of-the-art work-up had their ICM implanted by a stroke physician within 14 days after symptom onset. All patients were followed clinically and by rhythm monitoring for 12 months. AF was defined by detected atrial arrhythmia episodes ≥ 2 min, and these patients were considered for a change of their secondary prevention from antiplatelet drugs to oral anticoagulants (OAC). Results: A total of 259 patients with cryptogenic stroke or TIA from 18 hospitals in Norway, Sweden and Denmark were included. After 12 months follow-up 74 (28.6 %) patients were diagnosed with paroxysmal AF, of which 91.9% were asymptomatic. Patients with AF had significantly higher mean age (72.6 vs 62.2, p<0.001), more severe stroke (median National Institute Stroke Scale Score on admission 2 vs 1, p 0.002) and higher pre-stroke median CHA2 DS2 -VASc score (3 vs 2, p<0.001) than patients without AF. Both hypertension and hyperlipidemia was more common in patients with AF. In 64 (86.5%) cases AF was detected early after index stroke, i.e., within the first two months of monitoring (mean 47.7 days + 52, 1). Recurrent AF episodes were detected in 68 (91.9%) cases. Of the 74 AF patients, 72 (97.3%) were switched to OAC. Recurrent strokes during follow-up occurred in 2 AF patients (2.7 %) and in 9 non-AF patients (4.9 %). Conclusion: AF was detected in 29% of all cryptogenic stroke/TIA patients. Most of the patients were asymptomatic for their arrhythmia, and would have gone undiagnosed without a continuous monitoring approach. Since most of the patients with detected AF were switched to OAC, the 12 months risk of recurrent stroke in this group was low. Prolonged cardiac rhythm monitoring with ICMs is an effective tool for diagnosing underlying asymptomatic AF in a patient population typically confined to a stroke unit.